Business Analysis And Tofu Marketing (Case Study on XYZ Tofu Industry in Bukit Peninjauan 1 Village Sukaraja District Seluma Regency) - Nur Hidayah; Reswita Reswita; Ellys Yuliarti (SINTA Journal (Science, Technology, and Agricultural), 2021)
This study was aim to find out the amount of income of tofu industry in Bukit Peninjauan1 Village, Sukaraja District, Seluma Regency, the break-even point of tofu industry in Bukit Peninjaun 1 Village, Sukaraja District, Seluma Regency, the profitability of tofu industry in Bukit Peninjauan 1 Village, Sukaraja District, Seluma Regency, the marketing channel and marketing margin of the tofu industry in Bukit Peninjauan 1 Village, Sukaraja District, Seluma Regency. Profit in  XYZ Tofu Tofu Industry is Rp.36.209.079/month. The break-even point of XYZ Tofu Industry  for white tofu is 5,3 Mould and sales of Rp.224,693, while fried tofu is 99Mould with sales of Rp.3.460.431.The profitability of XYZ Tofu Industry  consists of ROI 0,24 and ROE 0,25.There are two marketing channels, namely:1) poducer, consumers and 2) producer, wholesalers, consumers while the total marketing margin is Rp.6.400 for white tofu and Rp.8.200 forfried tofu.